Massive infestation by Ascaris lumbricoides of the biliary tract: report of a successfully treated case Infestação maciça por Ascaris lumbricoides nas vias biliares: relato de um caso tratado com sucesso - Dahir Ramos de Andrade Júnior; José Abi Karam; Maria do Patrocínio Tenório Nunes Warth; Alexandre Frederico de Marca; José Jukemura; Marcel Cerqueira Cesar Machado; Antonino dos Santos Rocha (Revista do Instituto de Medicina Tropical de São Paulo, 1992)
This is a report of a 25 years old black woman from the city of São Paulo, Brazil, who developed acute obstructive cholangitis of Ascaris lumbricoides with septicemia and multiple hepatic abscesses. The patient had sickle cell trait and normal delivery 3 months ago. Massive infestation of the biliary tract by Ascaris lumbricoides was diagnosed by abdominal ultrasonography and endoscopic retrograde cholangiography. Sixty worms were removed from the common bile duct and hepatic abscesses were drained by surgery. The infectious process was polymicrobial. The patient's recovery was complete after a long evolution with a wide spectrum antibiotic therapy. New surgeries were needed to remove residual worms in the biliary tract. The diagnostic methods, clinical-biochemical features and also the clinical and surgical management are presented. The biliary ascariasis pathophysiology is commented. Descrito caso de mulher de 25 anos, negra, procedente da cidade de São Paulo - Brasil, que desenvolveu quadro agudo de colangite obstrutiva por Ascaris lumbricoides, com septicemia e múltiplos abscessos hepáticos. Era portadora de traço falciforme e tinha tido um parto normal há 3 meses. Foi estabelecido o diagnóstico de infestação maciça por Ascaris lumbricoides em vias biliares com ultrasonografia abdominal e colangiografia retrógrada endoscópica. Sessenta vermes foram retirados do colédoco e drenados os abscessos hepáticos por cirurgia. O quadro infeccioso era polimicrobiano. Houve recuperação total da paciente após longa evolução, com antibioticoterapia de amplo espectro e novas cirurgias com extração de vermes residuais. Os autores apresentam os métodos diagnósticos empregados, o quadro clínico-bioquímico e a abordagem terapêutica. A fisiopatologia da ascaridíase biliar é discutida.